Mathematical models in agriculture [ quantitative methods for the plant, animal and ecological sciences - Thornley, J. H. M. (CABI, 2007)
Bringing together the disciplines of agriculture, animal science, plant science and ecology, this book explores how mathematics can be used to understand and explain agricultural processes. It starts by providing a review of the mathematical models currntly available to agriculturalists, and the philosophy behind, and objectives of, modeling. The book then applies these techniques to real-life problems faced by people managing crops and animals, including the influence of digestion on animal growth rates and levels of photosynthesis on crop yield.